Anatomical Findings in Patients Undergoing Total Hip Arthroplasty for Idiopathic Femoral Head Osteonecrosis. (20th April 2016) - Ollivier, Matthieu; Lunebourg, Alexandre; Abdel, Matthew P.; Parratte, Sébastien; Argenson, Jean-Noël
Abstract : Background: Osteonecrosis of the femoral head has a host of etiologies. However, in 30% of the cases, no underlying etiology is identified and the process is considered "idiopathic." Our hypothesis was that osseous anatomical abnormalities might be frequently found in patients with femoral head osteonecrosis. Methods: A retrospective, 1:2 matched, case-control study was undertaken to compare ninety patients with idiopathic osteonecrosis who had undergone lower-limb computed tomography (CT) prior to undergoing total hip arthroplasty with 180 control patients matched for age, sex, and body mass index (BMI) who had undergone lower-limb computed tomography scanning at our radiology department for any reason except articular or bone disease. Preoperative CT scans were performed for all patients to evaluate femoral offset, femoral neck-shaft angle, femoral neck version, femoral head diameter, acetabular coverage estimated with use of the lateral center-edge angle, acetabular version, and acetabular diameter. The mean age was forty-five years, 69% of the patients were men, and the mean BMI was 26 kg/m 2 . Results: Anatomical "abnormalities" associated with osteonecrosis were determined to be a femoral neck-shaft angle of <129° (likelihood ratio [LR] = 3.6), femoral neck version of >17° (LR = 3.8), a lateral center-edge angle of <32° (LR = 5.7), and acetabular version of <19° (LR = 1.38). A combination of three of the four anatomical "abnormalities" was found in 73% of the patients with osteonecrosis but only 11% of the control cases (LR = 6). Conclusions: This 1:2 matched, anatomical study suggests that acetabular and femoral anatomical factors, in isolation or combination, can be found in a large percentage of cases of "idiopathic" osteonecrosis. Clinical Relevance: In this study, isolated or combined abnormalities of the hip were observed in the group of patients with osteonecrosis. Those elements may help surgeons to understand the process underlying idiopathic osteonecrosis and thus require further investigation.